The Effectiveness of Visualization Techniques and Mental Log Journaling in Enhancing the Mental Toughness of a Karate Athlete: A Case Study - Sa'idatur, Dhevi; Dewitasari, Rofi'ati Shefia; Agatha R. S., Chorry Elvira; Susanti, Ruth Natalia; Mayangsari, Dewi (Yayasan Sinergi Kawula Muda, 2025)
The problem of mental toughness in student athletes is an important concern because it directly influences the achievement of optimal performance. This research aims to increase mental toughness through psychological interventions based on visualization and journaling techniques. The research subject was a female karate student who showed symptoms of low self-confidence, difficulty in managing emotions, and anxiety when competing. The research was conducted in three intervention sessions carried out in three meetings. Each session consists of guidance on filling out a mental log, positive visualization exercises, and reflective journal writing. Measurements were carried out before and after the intervention using the mental toughness questionnaire. The research results showed an increase in mental toughness scores from the moderate to very tough category, as well as an increase in self-confidence, emotional management, and performance during training. These findings indicate that visualization and journaling techniques are effective in supporting the strengthening of mental toughness in student athletes.